Optimizing Supply Chain Distribution using Cloud based Autonomous Information - Shalini Gupta; Erick Jones (International Journal of Supply Chain Management, 2014)
The volume of the data and information traffic generated in warehouse management operations is extremely high. They are driven by such frequent events as attempts to locate inventory status files, associated inventory location and integration of specific customer order status tables (such as order payment, and order fulfillment status). The information technology infrastructure required to handle large data volume is expensive with additional cost for complex operations, limiting the operations of small businesses. In addition, any compromise with the infrastructure design may have further implications on the data storage and retrieval affecting productivity. In this research, we seek to investigate the feasibility of a Cloud-based warehouse management system (WMS) that continuously and autonomously captures RFID tagged inventory and distributes data handling processes. The purpose of this research paper is to investigate a RFID based WMS (R-WMS) application for mobile devices, including smart phones (such as iPhone, Android, Microsoft Mobile Phone, HTC smart phone, Blackberry, etc) and other handhold smart devices (such as iPad and some light/portable TabletPC) exchanging real-time information through the cloud which is being used to make near optimal decisions and send information back in an acceptable time period. In order to research these possibilities, there is a need to investigate the capacity and dynamic adjustment of workloads for reducing costs and saving energy. Further development of a mobile application of such data intensive operations necessitates exclusive multiple regression data manipulating techniques to provide the most critical information for decision makers. The broader impact of this research paper is the enhancement of mobile user capabilities driving improved productivity. This research will also add to the development of novel warehouse management techniques impacting world-wide business operations helping to realize the world is flatter than anticipated. Further, this multi-disciplinary research will enhance the Computer Science, Industrial and Systems Engineering curriculums by providing greater exposure to emerging areas in supply chain management, mobile computing, operations research, and cloud architecture and computing. The intellectual merit from this research will include ramifications on cloud-based mobile computing, which is the future of modern business operations. This research will train undergraduate and graduate students from both computer science and industrial engineering in the field of supply chain, logistics, mobile computing, and cloud computing. Keywords RFID WMS, Mobile applications; Cloud Computing;